2011
DOI: 10.1007/s12011-010-8944-2
|View full text |Cite
|
Sign up to set email alerts
|

Study on Blood Biochemical Diagnostic Indices for Hepatic Function Biomarkers in Endemic Skeletal Fluorosis

Abstract: The aim of the study was to determine the relationship of fluoride in drinking water to liver function in individuals living in normal and seven endemic fluorosis areas of Punjab, India. The concentration of fluoride in drinking water of different areas varied from 5.9 to 24.5 mg/L. Study group consisted of 705 patients in the age group between 20 and 60 years (mean age of 39.35±11.27) affected with osteodental fluorosis were compared with 300 age- and sex-matched controls (with mean age of 35.28±8.25 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Although fluorine is an essential mineral element for all mammals, including humans, exposure to high fluorine levels has toxic effects on various organs and tissues [ 1 ]. Fluorine, which is added to drinking water, is rapidly absorbed by the gastrointestinal tract after ingestion [ 2 ]. Other common sources of fluorine include dental products, food, drugs, and industrial emissions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although fluorine is an essential mineral element for all mammals, including humans, exposure to high fluorine levels has toxic effects on various organs and tissues [ 1 ]. Fluorine, which is added to drinking water, is rapidly absorbed by the gastrointestinal tract after ingestion [ 2 ]. Other common sources of fluorine include dental products, food, drugs, and industrial emissions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that F can cause progressive degeneration of the structure and functions of skeletal muscles, the brain, and the spine. In addition, it increases the aerobic metabolism and promotes alterations in the metabolism of cellular free radicals in several organs such as the liver, kidneys, and heart [6][7][8][9][10]. Free radicals cause toxicity by attacking membrane phospholipids, leading to membrane injury through lipid peroxidation, depolarization of the mitochondrial membrane, and apoptosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its well-known effects on the skeleton and teeth, fluorosis can also adversely affect soft tissues, such as the liver and kidneys [1,2]. The mechanisms by which fluoride produces such effects are still not clear.…”
Section: Introductionmentioning
confidence: 99%